Curating the reviled, beloved and quotidian: a retrospective of Vladimir Tretchikoff - Lamprecht, Andrew Paul (Rhodes University, Faculty of Humanities, Department of Fine Art, 2011)
This thesis aims to contextualise my curation of 'Tretchikoff: The People's Painter' at the Iziko South African National Gallery by outlining the process by which I came to embark on this project and to examine the concepts of mass art and kitsch in relation to the painter. Mass art, in Noel Carroll's explication of the term, is art that utilises industrial processes of replication. Carroll argues that this leads to specific formal and structural tendencies in this art which have much in common with the pejorative concept of kitsch, or art that is lacking in taste or effuses excessive emotion. The latter term was and continues to be applied to Tretchikoff. Although some have attempted to 'reclaim' the word as a positive concept the negative associations that link this term to Tretchikoff are strong. Interrogating these concepts led me to decide to curate TretchikofPs retrospective by focusing on his painting and not including the prints for which he was so well known. Awareness of the complex associations and 'received knowledge' that his prints engender has influenced several curatorial decisions that I have taken. I consider the intellectual underpinnings of my curatorial strategy and argue for an 'open' exhibition which gives the viewer the opportunity to assess his work and legacy in an objective manner, free from as much curatorial mediation and didacticsm as possible. There are no answers to be offered in my curation of Tretchikxiff the People's Painter, rather I have aimed to set up dialogues, discussions, confrontations and challenges; I have offered simple relationships rather than complex juxtapositions I have aimed to position the artwork as the centre of the engagement relative to the viewer.
Keywords: Tretchikoff, Vladimir -- Criticism and interpretation; Painters -- South Africa -- Criticism and interpretation; Curatorship -- South Africa -- Art; Kitsch